2008
DOI: 10.1111/j.1540-8167.2008.01211.x
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Death in a Young Man with Catecholaminergic Polymorphic Ventricular Tachycardia and Paroxysmal Atrial Fibrillation

Abstract: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a familial condition that presents with exercise-induced syncope or sudden death in children or young adults. In most cases the disease is caused by a mutation in the cardiac ryanodine receptor (RyR2) gene. Current evidence suggests that primary therapy for CPVT is beta blockade and implantable cardioverter defibrillator (ICD) placement. There is a recent report of a patient with CPVT who died despite appropriate ICD therapies, and we report a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 12 publications
0
68
0
Order By: Relevance
“…According to this double-hit concept, the AF substrate could be a genetic mutation (for instance, in RyR2) or atrial remodeling (electrical or structural). Three recent studies have demonstrated evidence for AF under certain circumstances in patients with genetic defects in the Ryr2 gene (37)(38)(39), albeit genetic forms of RyR2-mediated AF are not very common. In addition, enhanced CaMKII phosphorylation of RyR2 was confirmed in atrial biopsies from mice with atrial enlargement and spontaneous AF development, goats with lone AF, and patients with chronic AF.…”
Section: Figurementioning
confidence: 99%
“…According to this double-hit concept, the AF substrate could be a genetic mutation (for instance, in RyR2) or atrial remodeling (electrical or structural). Three recent studies have demonstrated evidence for AF under certain circumstances in patients with genetic defects in the Ryr2 gene (37)(38)(39), albeit genetic forms of RyR2-mediated AF are not very common. In addition, enhanced CaMKII phosphorylation of RyR2 was confirmed in atrial biopsies from mice with atrial enlargement and spontaneous AF development, goats with lone AF, and patients with chronic AF.…”
Section: Figurementioning
confidence: 99%
“…Indeed, ICDs have not prevented sudden death in several patients, often because of exhausted therapies after arrhythmic storms or inappropriate discharges triggered by supraventricular tachycardias. 10,11 Recently, preliminary data have suggested the potential value of combination drug therapy involving β-blockers and flecainide, but definitive evidence is still lacking. 12,13 In 2008, we demonstrated that left cardiac sympathetic denervation (LCSD) was quite effective in 3 patients with CPVT who continued to experience ventricular fibrillation and aborted cardiac arrest (ACA) despite full-dose β-blockers.…”
Section: Editorial See P 2169 Clinical Perspective On P 2193mentioning
confidence: 99%
“…Median age at LCSD was 15 years (IQR, 11-17 years), with no difference between symptomatic and asymptomatic patients. The approaches were mostly thoracoscopic (45, 71%) and supraclavicular (13, 21%), and LCSD was complete (from T1-T4) ≥1 end-of-treatment condition 5 (9) Age at first symptom, median (IQR), y 8.5 (6)(7)(8)(9)(10)(11) Age at diagnosis, median (IQR), y 9 (7-14)…”
Section: Lcsd Surgerymentioning
confidence: 99%
“…In situations with excessive intracellular Ca 2ϩ load, this electrogenic exchange generates a depolarization recognized as a DAD (183,295,434,503). Intracellular Ca 2ϩ overload can be subsequent to Ca 2ϩ leak from mutant ryanodine receptors (RyR) in the sarcoplasmic reticulum, which can result in catecholaminergic polymorphic ventricular tachycardia and concomitant fibrillation (347). Hyperphosphorylation of RyR as a consequence of increased sympathetic drive can also provoke phase 4 Ca 2ϩ overload and DADs (106).…”
Section: A Triggers Of Arrhythmiasmentioning
confidence: 99%